FARM INVESTMENT IN POLAND UNDER CONDITIONS OF ECONOMIC CHANGES IN SELECTED AGRICULTURAL MARKETS - Szymańska, Elżbieta Jadwiga; Dziwulski, Mariusz (Acta Scientiarum Polonorum. Oeconomia, 2021)
The aim of the research was to determine changes in the level of investments in fixed assets on Polish farms with different types of production in the context of changes in the economic situation on selected agricultural markets in Poland. The research used studies of the literature on the subject and the mass statistics data of Poland’s Central Statistical Office. A detailed analysis covered 878 farms which in 2005–2013 kept continuous accounting under the FADN system and did not change the direction of production. They were grouped into three categories depending on their specialization: cereal, dairy and pig. The study formulated a research hypothesis that production profitability affects farm investments. The research used a comparative analysis of changes in economic results on farms in 2005–2013 and the Pearson’s linear correlation method. Results show that the scale and nature of investments in farms with different production directions were diversified and changed in the following years. To a large extent, changes in investments depended on changes in the profitability of production in single agricultural markets, which confirms the formulated hypothesis. Pig farms were characterized by the greatest sensitivity of changes in investments to changes in the price situation in agricultural markets. The possibilities of co-financing investments and their long-term nature mitigated the impact of shock changes on the investment dynamics.